PENERAPAN KOMUNIKASI TERAPEUTIK PADA PASIEN HALUSINASI DI RUMAH SAKIT JIWA TAMPAN PROPINSI RIAU - Widiyanto, Juli; Rizki, Zakiyah (Sistem Informasi, 2016)
Therapeutic communication is a communication made by nurses to patients who previously had been planned in advance. Therapeutic Communication aims to reduce the burden of perceived or experienced by the patient. While hallucination is a perception disorder that does not actually exist in reality. With the Application of Therapeutic Communication will be an alternative to overcome the problems associated with hallucinations patients. Aim of study is to look at describe Application of Therapeutic Communication Hallucinations in Patients at the Tampan Mental Hospital of Riau Province. Kind of Research used is simple description with time series desain and the sampling technique is simple random sampling technique whice are mostly nurses samples in this study who were at the Tampan Mental Hospital of Riau province are 38 respondents. The Instrumen to tool uses observation sheets and indepth interview. The Results of research has been indicated that describe Application of Therapeutic Communication in Patients Hallucinations at The Tampan Mental Hospital of Riau Province mayoritas is applied therapeutic communication as much as 24 respondents (63.2%) whereas in the category does not apply as much as 14 respondents (36.8%). Based on the results of these studies are expected to nurses at the Tampan Mental Hospital of Riau Province to improve the application of therapeutic communication is done to patients who experience mental illness of his special patients experiencing hallucinations.